Setting of norms of physical loadings by students' self-appraisal of level of bodily condition and capacity - Griban G.P (Kharkov National Pedagogical University, 2012)
The ways of study of terms for creation of individualization and differentiation of physical education of students are considered. A purpose of work is study of possibilities of the use of self-appraisal of students of physical eigenstate for planning of the physical loadings in employments on physical education. 647 students took part in experiment. Students defined an own physical capacity the method of questionnaire. It is set that students are well oriented and can define the physical capacity. Cross-correlation connection is marked between the indexes of physical preparedness of students on results a questionnaire and to the results of measuring. It is marked that exists substantial difference in the self-appraisal of capacity in different educational separations. It is set that ability of students is independent allows to estimate the level of the capacity a teacher operatively to bring in correction in an educational process. Also to determine a volume, intensity of the physical loadings, periods of rest, manage the process of physical perfection of students.